Efficiency of Antimicrobial Peptides Against Multidrug-Resistant Staphylococcal Pathogens - Le, Mi Nguyen-Tra; Kawada-Matsuo, Miki; Komatsuzawa, Hitoshi (Frontiers in Microbiology, 2022)
Antibiotics play a vital role in saving millions of lives from fatal infections; however, the inappropriate use of antibiotics has led to the emergence and propagation of drug resistance worldwide. Multidrug-resistant bacteria represent a significant challenge to treating infections due to the limitation of available antibiotics, necessitating the investigation of alternative treatments for combating these superbugs. Under such circumstances, antimicrobial peptides (AMPs), including human-derived AMPs and bacteria-derived AMPs (so-called bacteriocins), are considered potential therapeutic drugs owing to their high efficacy against infectious bacteria and the poor ability of these microorganisms to develop resistance to them. Several staphylococcal species including Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus haemolyticus, and Staphylococcus saprophyticus are commensal bacteria and known to cause many opportunistic infectious diseases. Methicillin-resistant Staphylococci, especially methicillin-resistant S. aureus (MRSA), are of particular concern among the critical multidrug-resistant infectious Gram-positive pathogens. Within the past decade, studies have reported promising AMPs that are effective against MRSA and other methicillin-resistant Staphylococci. This review discusses the sources and mechanisms of AMPs against staphylococcal species, as well as their potential to become chemotherapies for clinical infections caused by multidrug-resistant staphylococci.